Hydrogen separation and production using proton-conducting ceramic membrane catalytic reactors - Seo, Minhye; Park, Eun Duck (Korean Chemical Engineering Research, 2019)
Proton-conducting perovskite ceramic materials are highly promising for solid electrolytes as well as catalysts at high temperatures. Therefore, they possess an outstanding potential for the membrane reactor in which both reaction and separation occur at a same time. Especially, in the case of hydrogen production catalyst, hydrogen separation, and the membrane reactor coupled with catalyst and separation, extensive results have been reported on the effect of the dopant in the solid electrolytes, temperature, and composition of reactants on the performance. In this review, the recent research trend on the application of proton-conducting ceramic materials to hydrogen production catalyst, hydrogen separation, and membrane reactor is surveyed. Moreover, the potential application and prospect of these materials to the next-generation hydrogen production and separation is discussed.
Keywords: Catalytic membrane reactor; Hydrogen separation; Membrane; Perovskite; Proton-conducting ceramics